OPTIMALITION OF NATURAL LIGHTING IN LECTURE BUILDING FACULTY OF ADMINISTRATION SCIENCE, BRAWIJAYA UNIVERSITY, MALANG - merdi - zuhendra; Andika - Citraningrum (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
This research aims to analyze the impact of natural lighting in the Faculty of Administrative Science, Brawijaya University classrooms in the City of Malang. A school is a place for learning used by teachers and students. The existence of comfortable lighting is important for maintaining concentration during the learning process. By using natural lighting, it is expected that the need for lighting in classrooms. However, there are differences in room’s function, area, height and orientation. The campus building has a typical shape of windows and shading device for each room. The shape of the building’s opening is quite different usual in that the difference is on the placement of the windows that are inwards, resembling the letter “U”, which indirectly forms a combination of vertical and horizontal shading device. The method used in this research is quantitative and experimental with dimension variable, shape of windows, shading device, floor color, wall color, ceiling color, furniture placement, degree of natural lighting and natural light distribution. The recommendations included in the research are related to the research variables.Keywords: Natural Lighting, Classrooms, Openings, Simulation